STUDENTS’ PERCEPTION OF USE ORAI APPLICATION IN TEACHING ENGLISH SPEAKING AT SMPN 1 SIMANINDO - Ruth Dannesh Siallagan; Tiarma Intan Marpaung; Febrika Dwi Lestari (Jurnal Scientia, 2022)
Orai application is an application that can help students in developing speaking in English. The aims of the study to know students’ perception of use Orai application in teaching Englsih speaking at SMPN 1 Simanindo. In this study, the instruments of collecting data are used by observation and interview sheet. The Observation was used to observe English teaching and learning activities in the use of the Orai application. The interview sheet consists of ten questions regarding students' perceptions of using the Orai application. Sources of data in this study were taken from students of eighth-grade. There are fifteen students who have filled out the interview questions given. This study used a qualitative descriptive design. The findings from data analysis, students have positive and negative perceptions in the use of the Orai application as a media in learning English. Orai application is an application that helps students improve pronunciation in speaking English. In using the Orai application, students feel happy and more confident because it makes it easier for students to learn English. Orai application is an application that is able to develop students' speaking for the better.